2022
DOI: 10.3390/foods11040610
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pulsed Electric Fields on the Lipidomic Profile of Lipid Extracted from Hoki Fish Male Gonad

Abstract: Processing of hoki, a commercially important fish species, generates substantial quantities of co-products, including male gonad, which contains valuable lipids, such as phospholipids, that could be recovered and utilised. Hoki fish male gonads (HMG) were subjected to pulsed electric fields (PEF) treatment at varying field strengths (0.625, 1.25, and 1.875 kV/cm) and frequencies (25, 50, and 100 Hz), at a fixed pulse width of 20 μs. The total lipid was extracted using an ethanol-hexane-based (ETHEX) extraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Similarly, many studies have also shown that PC and PE were the dominant kinds of PLs in the by‐products of marine animals, and their contents in female organisms were higher than those in male ones. [ 35–38 ]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, many studies have also shown that PC and PE were the dominant kinds of PLs in the by‐products of marine animals, and their contents in female organisms were higher than those in male ones. [ 35–38 ]…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table 3, lipids extracted from abalone gonads were abundant in palmitic acid (C16:0), which was also the most common saturated FA found in tissues of most marine organisms. [ 37 ] According to Gabbott, [ 42 ] in addition to being the primary end product of the FA synthetase system in animal tissues, this FA is the precursor for the de novo synthesis of long‐chain FAs. Besides, the contents of PUFA were shown as follows: LFG, 14.42% ± 1.20% of total FAs; LMG, 18.27% ± 0.33% of total FAs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Especially under optimum PEF treatment conditions, 53.3% of phospholipids were extracted from male fish gonads. The extracted compounds have the potential to treat chronic disorders such as neurodegenerative disorders, cardiovascular diseases, diabetes, and so it can be used in nutraceutical applications (Burnett et al, 2022) (Fig. 4).…”
Section: Lipids and Carotenoidsmentioning
confidence: 99%